Pengaruh Loan To Deposit Ratio Dan Biaya Operasional Pendapatan Operasional Terhadap Return On Assets Pada PT. Bank Negara Indonesia (Persero), tbk. - Andi Sartika Juniarmita; Ahmad Latando Paturusi (Jurnal Online Manajemen ELPEI, 2023)
The purpose of this study was to determine the effect of the loan to deposit ratio and operational costs of operating income on Return On Assets at PT. Bank Negara Indonesia (Persero), Tbk. The type of data used in this research is quantitative data. Source of data used in this research is secondary. The data analysis method used is descriptive analysis, multiple linear regression, r, r, t test and F test. From the results of the research that has been done, the results of the equation are Y = 5.93 + 0.03 X1 - 0.089 X2. Partially the loan to deposit ratio has a positive and insignificant effect on return on assets, for operational costs and operating income it has a negative and significant effect, and simultaneously a significant effect on return on assets at PT. Bank Negara Indonesia (Persero), Tbk